1990
DOI: 10.1128/jb.172.11.6308-6315.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, mapping, and sequencing of the gene encoding Escherichia coli quinoprotein glucose dehydrogenase

Abstract: Escherichia coli contains pyrroloquinoline quinone-dependent glucose dehydrogenase. We cloned and sequenced the gene (gcd) encoding this enzyme and showed that the derived amino acid sequence is highly homologous to that of the gdhA gene product of Acinetobacter calcoacetcus. Stretches of homology also exist between the amino acid sequence of E. coil glucose dehydrogenase and other pyrroloquinoline quinonedepenent dehydrogenases from several bacterial species. The position of gcd on the chromosomal map of E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(58 citation statements)
references
References 36 publications
0
58
0
Order By: Relevance
“…The D-glucose dehydrogenase in G. suboxydans IFO 3255 was diŠerent from SLDH, although the amino acid sequence of SLDH 7) was moderately similar to that of D-glucose dehydrogenases. [8][9][10] The diŠerence between SLDH and D-glucose dehydrogenase could be predicted from the substrate speciˆcity of puriˆed SLDH, which is inactive toward D-glucose. 6) The defects in dehydrogenase activity against Dsorbitol, D-mannitol, and glycerol in 3255sldA::Km cells were complemented by the introduction of pVKSLP carrying the sldA and sldB genes or pTNB136 carrying only the sldA gene (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The D-glucose dehydrogenase in G. suboxydans IFO 3255 was diŠerent from SLDH, although the amino acid sequence of SLDH 7) was moderately similar to that of D-glucose dehydrogenases. [8][9][10] The diŠerence between SLDH and D-glucose dehydrogenase could be predicted from the substrate speciˆcity of puriˆed SLDH, which is inactive toward D-glucose. 6) The defects in dehydrogenase activity against Dsorbitol, D-mannitol, and glycerol in 3255sldA::Km cells were complemented by the introduction of pVKSLP carrying the sldA and sldB genes or pTNB136 carrying only the sldA gene (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…We cloned the gene encoding the SLDH of G. suboxydans IFO 3255, sldA, and found that it encoded a polypeptide of 740 amino acid residues including a signal sequence of 24 residues. 7) The polypeptide had 35-37z homology with the membrane-bound and PQQ-dependent D-glucose dehydrogenases of G. oxydans, 8) Acinetobacter calcoaceticus, 9) and Escherichia coli 10) everywhere but the hydrophobic N-termini. We found one open reading frame directly upstream of the gene sldA; this gene, sldB, encoded a polypeptide of 126 amino acid residues that was hydrophobic and had a sequence similar to the hydrophobic N-termini of D-glucose dehydrogenases.…”
Section: )mentioning
confidence: 99%
“…The glucose dehydrogenase is also inhibited by piericidin A competitively with regard to ubiquinone [112]. The amino acid sequence is known for the enzyme of Acinetobacter calcoaceticus [I151 and E. coli [116]. Only the N-terminal region of the sequence is hydrophobic enough to span the mem- brane.…”
Section: Subunits Of the Membrane Partmentioning
confidence: 99%
“…This sequence is a specific region in the genomic DNA of Escherichia coli for pyrroloquinoline quinone-containing glucose dehydrogenase [EC 1.1.99.17], corresponding to 1135-1166th bases that encode 379-389th amino acid residues (15).…”
Section: Target and Probe Oligonucleotidesmentioning
confidence: 99%